Analisis Efektivitas Dan Kontribusi Penerimaan PKB Dan BBNKB Terhadap Pendapatan Asli Daerah Provinsi Sumatera Utara - Della Audia Saputri; Rahmd Daim Harahap (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2022)
Analysis of the Effectiveness and Contribution of PKB and BBNKB Revenues to the Regional Original Revenue of North Sumatra Province. This study aims to determine the Effectiveness and Contribution of Motor Vehicle Tax Revenue (PKB) and Motor Vehicle Transfer Fees (BBNKB) to Regional Original Income (PAD) at the Regional Tax and Levy Management Agency of North Sumatra. The research method uses a descriptive approach. Using data on the realization of PKB and BBNKB receipts in 2017-2021. The results showed that the level of effectiveness of PKB in Medan City in 2017-2021 with an average of 105.49% and the level of effectiveness of BBNKB with an average of 106.32%, the effectiveness of PKB and BBNKB is included in the very effective criteria. Then it generates original regional income for 2017-2021 PKB with an average of 42.73% included in the good criteria, while local original income for 2017-2021 BBNKB with an average of 26.01% is included in the sufficient criteria.